Stem cell sources for tooth regeneration: current status and future prospects - Otsu, Keishi; Kumakami-Sakano, Mika; Fujiwara, Naoki; Kikuchi, Kazuko; Keller, Laetitia; Lesot, Hervé; Harada, Hidemitsu (Frontiers in Physiology, 2014)
Stem cells are capable of renewing themselves through cell division and have the remarkable ability to differentiate into many different types of cells. They therefore have the potential to become a central tool in regenerative medicine. During the last decade, advances in tissue engineering and stem cell-based tooth regeneration have provided realistic and attractive means of replacing lost or damaged teeth. Investigation of embryonic and adult (tissue) stem cells as potential cell sources for tooth regeneration has led to many promising results. However, technical and ethical issues have hindered the availability of these cells for clinical application. The recent discovery of induced pluripotent stem (iPS) cells has provided the possibility to revolutionize the field of regenerative medicine (dentistry) by offering the option of autologous transplantation. In this article, we review the current progress in the field of stem cell-based tooth regeneration and discuss the possibility of using iPS cells for this purpose.